Advanced Microarrays as Heterogeneous Force‐Remodeling Coordinator to Orchestrate Nuclear Configuration and Force‐Sensing Mechanotransduction in Stem Cells - Wang, Nana; Hou, Yan; Lin, Lili; Xu, Shihui; Lee, Kyubae; Yang, Yingjun; Chen, Yazhou; Li, Yachun; Wang, Xiuhui; Wang, Yongtao; Chen, Tao (Advanced science, 2025)
Integrin and focal adhesion can regulate cytoskeleton distribution to govern actin‐related force remodeling and play an important role in nuclear configuration and force‐sensing mechanotransduction of stem cells. However, further exploration of the interaction between actinin complex and myosin, kinetics, and molecular mechanism of cytoskeleton structures to nucleate within the engineered stem cells is vague. An extensive comprehension of cell morphogenesis, force remodeling, and nuclear force‐sensing mechanotransduction is essential to reveal the basic physical principles of cytoskeleton polymerization and force‐related signaling delivery. Advanced microarrays are designed to determine heterogeneous cell morphology and cell adhesion behaviors in stem cells. The heterogeneity from the engineered microarrays is transferred into nuclei to regulate nuclear configuration and force‐sensing mechanotransduction by the evaluation of Lamins, YAP, and BrdU expression. Tuning the activation of adhesion proteins and cytoskeleton nucleators to adjust heterogeneous cell mechanics may be the underlying mechanism to change nuclear force‐sensing configuration in response to its physiological mechanotransduction in microarrayed stem cells. Engineered microarrays are prepared by the photolithography and further decorated via fibronectin protein to determine the morphogenesis of stem cells. Heterogeneous integrin expression and focal adhesion formation are regulated in microarrayed cells. Polar remodeling of cytoskeleton nanomechanics happens in the heterogeneous cells. Nuclear configuration circulation is explained through force‐sensing mechanotransduction by the evaluation of Lamins, YAP, and BrdU analysis.